Correlates of Homelessness Among Patients in Methadone Maintenance Treatment. Issue 11 (November 2020) - Gaeta, Marina; Beitel, Mark; Oberleitner, Lindsay M.S.; Oberleitner, David E.; Madden, Lynn M.; Tamberelli, Joseph F.; Barry, Declan T.
Abstract : Background: Although homelessness and opioid use disorder (OUD) are important public health issues, few studies have examined their cooccurrence. Objectives: The aim of this study was to evaluate the correlates of homelessness among patients enrolled in low-barrier-to-treatment-access methadone maintenance treatment (MMT) programs for OUD. Methods: Demographic, diagnosis-related, and treatment-related correlates were assessed by self-report for 164 patients in MMT. Correlates of past-month homelessness were investigated with logistic regression. Results: Twenty-four percent of patients reported homelessness in the past month. Bivariate analyses initially identified 7 statistically significant ( P <0.05) correlates of homelessness: gender; Latinx ethnicity; symptoms of depression, anxiety, and somatization; self-criticism; and duration of MMT. In the final logistic regression model, which included significant independent variables from the bivariate logistic regressions, patients in MMT who were homeless (vs. domiciled) were more likely to be male (odds ratio 2.54; confidence interval, 1.01–6.36) and report higher symptoms of depression (odds ratio 1.07; confidence interval, 1.01–1.15). Conclusions: Low-barrier-to-treatment-access programs can attract people who are homeless with OUD into MMT. These programs also have an important public health role in addressing both depression and OUD among people who are homeless.